THE EXAMINATION OF THE TURKISH ELEMENTARY FOURTH-GRADE MATHEMATICS TEXTBOOK REGARDING VALUES - Yusuf SÖZER; Sinan ÖNEL (MOJES: Malaysian Online Journal of Educational Sciences, 2023)
This study examines the current Turkish primary school 4th-grade Mathematics textbook through the core values settled in the curriculums to mediate relevant (sub)values by the Turkish Board of Education (BoE). The core and sub-values were investigated through the defined aspects of inclusion, intensity, reflection, and mediation status. This qualitative case-study research was done through document analysis. “Textbook Value Inclusion Form” was developed by the researchers to examine the contents in visual, problem text, and activity sections, and 155 visuals, 117 problems, and 46 activity contents were analyzed. The values were unevenly distributed, where the visuals were more intensive among the content types, while the natural numbers and fractions were more concentrated within the subjects. Consequently, the book mostly covered desired values, but missing and even degenerative contents were also encountered. The values did not reflect a balanced distribution regarding units and core values. The book predominantly reflected the values implicitly. Responsibility, respect, and helpfulness were prominent mediative core values throughout the book, and diligence, healthiness, productivity, collaboration, and tradition were the sub-values being significantly mediated. As a result, the textbook adequately covered particular values, though there were identified areas for improvement, and recommendations were given to address them.